(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article It is said that information technologies offer various new forms of education , in particular, the principle of the collective approach in the modular education system is gaining strength in recent times. In addition, various forms, methods, and the introduction of mixed education as an innovation and other aspects have been revealed.